Straightforward and rapid determination of acrylamide in coffee beans by means of HS-SPME/GC-MS. (15th December 2019) - Wawrzyniak, Rafał; Jasiewicz, Beata
Highlights: d3 -acrylamide as an internal standard reduces the costs of analysis of acrylamide in coffee beans. Presented method of sample preparation and determination of acrylamide is rapid. The used method demonstrates satisfactory precision, repeatability and accuracy. Abstract: A straightforward and rapid preparation procedure for the extraction of the acrylamide from coffee beans, by means of the volatile silylated derivatives of acrylamide (AA) and headspace solid phase microextraction (HS - SPME) is described. Commercially available SPME fibre coated with polydimethylsiloxane (PDMS) was used. The silylation reactions of the AA were executed with N, O- bis(trimethylsilyl)trifluoroacetamide (BSTFA). The deuterium labelled d3 -acrylamide was used as an internal standard. The acrylamide level was quantified using gas chromatography coupled with the mass spectrometry (GC-MS) in the selected ion monitoring (SIM) mode. The limit of quantification (LOQ) for measuring acrylamide was 3 µg/kg. The described method demonstrates satisfactory repeatability (RSD = 2.6%), with an intermediate precision (RSD = 9.4%) and recovery (99–105%).